CONTEMPLATION ON THE ETHICS OF SPORT (Fiep Bulletin - online, 2012)
This paper presents a discussion about sport as a complex phenomenon that generates ethicalcontradictions.Sport involves human primal, natural, cultural and technologically acquired needs andcapabilities. The ideology of technological progress plays an important role in the sports world.According to the author, ethical reasoning in sport cannot be expected to have a convincingpower, since pluralism of sporting practices (recreational, elite and extreme sport) implies pluralismof sports ethics. He attempts to avoid the slippery moralising ground that often accompanies moraljudgments in sports: no ethical position can be substantiated without intuitive and culturallydependent reasoning.The ethics of responsibility to fellow humans can also be understood as the ethics towardsnature. Although the sports ethics literature devotes much of the following to the relation betweenoneself and others, ethics is not only a question of human-human relations. It is more and more aquestion of human-nature relations, since sports activities are directly or indirectly engaged with thenatural environment. Based on this assumption, the author talks about "eco-ethics", the ethics ofnature. It places sport within the larger context of global environmental concerns. The ethical turn,which demands the re-evaluation of our relation towards nature must also embrace sport.The paper also discusses the development of a new theory of sport to be found in the gapbetween experience and reflection and between practice and theory.
Keywords: sports; ethics in sports; eco-ethics; sports theory.